This Quintessence of Dust - Consciousness Explained, at Thirty. (4th May 2021) - Warren, Jared
Abstract: Daniel Dennett's Consciousness Explained is probably the most widely read book about consciousness ever written by a philosopher. Despite this, the book has had a surprisingly small influence on how most philosophers of mind view consciousness. This might be because many philosophers badly misunderstand the book. They claim it does not even attempt to explain consciousness, but instead denies its very existence. Outside of philosophy the book has had more influence, but is saddled by the same misunderstanding. Now, 30 years after publication, Consciousness Explained deserves reconsideration from anyone interested in consciousness. Here I make a case for this. To start, I will clear up the central misunderstanding of the book. With that done, I will explain and update Dennett's tantalizing approach to consciousness and the mind. The result brings us very, very close to explaining consciousness. Or so I will argue.